On the translation of the epic-narrative genre - Martín Cerezo, Iván (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Because of the extent of the object of study to address, the scope of this article is to set out the main characteristics of the narrative literary texts throughout a theoretic frame, and its possible translation strategies prioritizing the signs that distinguish them.